Злочини, покарання та їх виконання у станицях Дунайського (Новоросійського) козацького війська (1828-1868 рр.): справа козака Івана Дульдієра - Бачинська, О. (Чорноморська минувшина, 2020)
У статті розглядаються основні види злочинів та покарань, які розглядала комісія Військового суду при Військовому правлінні Дунайського (Новоросійського) козацького війська. З’ясовано, що в багатьох випадках до втеч зі служби козаків провокували дії офіцерів, які, як правило, не несли за такі провокації жодних покарань. У додатках до статті публікуються документи однієї зі справ козака Івана Дульдієра, вчинки якого Комісія розглядала не одноразово. The question of the system of punishments, their adequacy to the crimes committed has become important today. Discussion of this issue is important not only for Ukraine but also for most countries of the world. This changes the view of both the crimes themselves and their assessment. The institution responsible for the execution of sentences imposed under the legislation currently being modernized in Ukraine is called the penitentiary service. Its operation and effectiveness often depend not only on global rules, codes and practices, but also on local traditions in the penitentiary system and their enforcement. Certain crimes of a moral and ethical nature are difficult to assess in terms of legal norms, and at different times may not be considered as crimes. The study of these traditions actualizes the historical experience that needs to be studied, in particular on the territory of Ukraine, in such organizations as Cossack societies and Cossack troops. These were paramilitary structures that have clearly defined rights, responsibilities, a system of punishment and their execution. However, even in these structures there were deviations from national rules. In this regard, the objectives of our publication is to show, on the example of one archival case, the causes of crimes, their nature and form, the figures of prosecuted Cossacks, punishments and their implementation that existed in real life of the Cossacks, one of the last Cossacks formations of the XIX century on the territory of modern Ukraine - the Danube (Novorossiysk) army. It was ascertained that the organization that considered the violations and served as a court in the Danube Cossack Army was a commission of the Military Court. It was determined that the main reasons for the lawsuits were the Cossacks' protests against the arbitrariness and abuse of officers and military officials, which manifested themselves in runaways, complaints, and so on. In some case, Officers and Cossacks were also the subject to trial for drunkenness and violation of moral and ethical norms.